(untitled) (Veterinary Science, 2017)
The hepatozoonosis is a parasitic disease caused by protozoa of the genus Hepatozoon spp. affecting primarily the dog, as well as other animal species. The definitive host is the brown tick, Riphicephalus sanguíneus, that transmits the disease when ingested by the intermediate host. Clinical symptoms are nonspecific and similar to those produced by other diseases most prevalent in the canine population. It is more severe in puppies less than 1 year of age and older dogs. The aim of this publication is to report the first cases of canine hepatozoonosis registered in the city of General Pico province of La Pampa. The presence of gametocytes of Hepatozoon canis was determined in whole blood drawn from forearm cephalic vein and colored smears with staining 15. All cases were from municipal canilera and were treated at the Small Animal Teaching Hospital, Faculty of Veterinary Science, National University of La Pampa and had a history of being infested with ticks. We can say that Hepatozoon canis is present in dogs City General Pico clinically and clinically incidence occurs with massive infestation of ticks of the genus Riphicephalus sanguineus. As important conclusion would determine disease prevalence for action protocols to control the hepatozoonosis and tick population.